2009
DOI: 10.1016/j.lungcan.2009.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Targeted reduction of KLF6-SV1 restores chemotherapy sensitivity in resistant lung adenocarcinoma

Abstract: Kruppel-like factor 6 splice variant 1 (KLF6-SV1) is an oncogenic splice variant of the KLF6 tumor suppressor gene that is specifically overexpressed in a number of human cancers. Previously, we have demonstrated that increased expression of KLF6-SV1 is associated with decreased survival in lung adenocarcinoma patient samples and that targeted reduction of KLF6-SV1 using siRNA induced apoptosis both alone and in combination with the chemotherapeutic drug cisplatin. Here, we demonstrate that chemoresistant lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…After the cells were either treated with a drug or transfected with siRNA, they were stained with propidium iodide to ascertain the DNA content and determine cell cycle distribution within the cell population as previously described (44). Sub-G1 peaks were analyzed on DNA histograms; hypodiploid DNA represented dead cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the cells were either treated with a drug or transfected with siRNA, they were stained with propidium iodide to ascertain the DNA content and determine cell cycle distribution within the cell population as previously described (44). Sub-G1 peaks were analyzed on DNA histograms; hypodiploid DNA represented dead cells.…”
Section: Methodsmentioning
confidence: 99%
“…A pSUPER vector encoding luciferase shRNA was used as a control. Stable cell lines of HCC827 were generated by retroviral transfection of the pSUPER-shLuciferase (shLuc) and pSUPER-shKLF6 (shKLF6) and selected with 2 μg/ml puromycin as described previously (44). Polyclonal pools of the shRNA-infected cell lines were collected, and KLF6 knockdown was determined by qRT-PCR and Western blotting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been shown that functional inactivation of KLF6 in various types of cancers such as prostate, ovary and colon, is caused by somatic mutations, loss of heterozygosity (LOH) and silencing by hypermethylation of its promoter Cho et al, 2006;Sangodkar et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of KLF6-SV1 contributes to chemo-resistance in lung cancer. Targeted reduction of KLF6-SV1 by RNA interference results in the induction of spontaneous apoptosis in cell culture synergizes with chemotherapeutic agents like cisplatin, and lead to significant tumor regression in vivo [21] . These observations emphasized the importance of investigation of alternative splicing genes in lung cancer for improving targeted therapy.…”
Section: Alternatively Spliced Genes As Therapeutic Targets In Lung Cmentioning
confidence: 99%